Low work-function tether Deorbit Kit. Issue 3 (September 2020) - Tarabini Castellani, L.; Ortega, A.; Giménez, A.; Urgoiti, E.; Sánchez-Arriaga, G.; Borderes-Motta, G.; Lorenzini, E.C.; Tajmar, M.; Wätzig, K.; Post, A.; Plaza, J.F.
Abstract: This works presents a system level analysis of a Deorbit Kit (DK) based on electrodynamic tether technology. The analysis is focused on two relevant scenarios for deorbiting space debris: (i) Earth Observation (EO) satellites with mass in the range of 700 kg -1000 kg and initial orbital altitude of 800 km and 98° inclination, and (ii) Mega Constellation (MC) spacecraft in the order of 200 kg and initial orbit at 1200 km of altitude and 90° of inclination. The scenarios have been selected considering the orbits that are already suffering from the space debris problem or will suffer in the next future. The DK implements a bare electrodynamic tether for capturing electrons passively from the ambient plasma while three different methods are considered for emitting the electrons back to the plasma to reach a steady electrical current on the tether. The three studied options to close the electrical circuit are: (a) a hollow cathode, which has a high technological maturity but needs expellant and a little of power, (b) a thermionic emitter, which does not involve expellant but needs power, and (c) a Low Work-function Tether (LWT) that does not need neither expellant nor power because it has a segment coated with a special material that emits electrons passively through the thermionic and photoelectric effects. In order to provide a fully autonomous operation even in case of critical failure of the mother spacecraft, the DK includes a deployment mechanism, a telemetry and telecommand system, a complete Attitude Determination and Control System with attitude sensors (GNSS, sun sensors, magnetometer) and actuators (magneto torquers), solar panels and batteries. Upon activation, the DK autonomously de-tumbles the satellite, deploys a tether and carries out the satellite's de-orbiting. The study presents DK architectures, mass budgets and simulation results for the two scenarios. It is shown that a complete DK with mass below 6% the mass of the host spacecraft can deorbit EO and MC satellites in about 1.5 years and 10 years, respectively. The importance of the development of the LWT concept to enhance the simplicity and reduce the mass, power and volume budget is highlighted.